The cultural studies reader - During, Simon (London ; New York : Routledge, 1999)
The first edition of <The Cultural Studies Reader> established itself as the leading textbook in the field, providing the ideal introduction for students to this exciting and influential discipline. This expanded second edition offers:
* 38 essays including 18 new articles
* an editor's preface succinctly introducing each article
* comprehensive coverage of every major cultural studies method and theory
* an updated account of recent changes in the field
* articles on new areas such as science and cyberculture, globalization, postcolonialism, public spheres and cultural policy
* a fully revised introduction and an extensive guide to further reading.
1. izd. 1993
Zastupljeni autori: Adorno, Theodor Wesegrund ; Barthes, Roland ; Steedman, Carolyn ; Clifford, James ; McRobbie, Angela ; Hall, Stuart ; Soja, Edward ; Certau, Michel de ; Foucalt, Michel ; Lyotard, Jean-François ; Abbas, A. ; Spivak, Gayatri Chakravorty ; Bhabha, Homi K. ; Forgacs, David ; Appadurai, Arjun ; hooks, bell ; Lott, Eric ; West, Cornel ; Haraway, Donna ; Ross, Andrew ; De Lauretis, Teresa ; Sedgwick, Eve Kosofsky ; Berlant, L. ; Warner, M. ; Dyer, R. ; Stallybrass, P. ; White, A. ; Morris M. ; Williams, Raymond ; Bourdieu, Pierre ; Hebdige, Dick ; Straw, W. ; Chow, R. ; Bennett, Tony ; Garnham, N. ; Hall, Stuart ; Fraser, Nancy ; Naficy, H. ; Radway, Janice A. ; Horkheimer, Max
Str. 577-599: Bibliografija
Kazalo
Keywords: kulturalni studiji; sociologija kulture